Unprecedented climate extremes in South Africa and implications for maize production. (1st August 2022) - Bradshaw, Catherine D; Pope, Edward; Kay, Gillian; Davie, Jemma C S; Cottrell, Andrew; Bacon, James; Cosse, Adriana; Dunstone, Nick; Jennings, Stewart; Challinor, Andrew; Chapman, Sarah; Birch, Cathryn; et al.
Abstract: Maize is the most important crop grown in South Africa, but yields can be severely reduced by extreme high summer average temperatures and low precipitation, potentially adversely affecting both domestic consumption and regional food security exports. To help understand and manage climate risks to food security in Southern Africa it is essential to quantify the present-day likelihood and magnitude of climate extremes in South Africa's maize-growing region and explore the potential for unprecedented climate conditions which would likely result in record low maize yields. We analyse a large ensemble of initialised climate model simulations, which provides almost 100 times as many plausible present-day summers as the equivalent observational dataset. We quantify the risk of unprecedented climate extremes affecting maize production in South Africa and examine the role of the El Niño-Southern Oscillation. We find that the South African maize region is at risk of experiencing record-breaking hot, cold, dry or wet events under current climatic conditions. We find that the annual chance of unprecedented high temperatures in South Africa is approximately 4%, increasing to 62% during very strong El Niño years. We also find that the chance of exceeding the present day seasonal high temperature record has increased across the 1979–2018 period, being five times more likely now than it was in 1980. These extreme events could result in a record-breaking number of days above the optimum, or even the maximum, temperature for maize production, and lead to more severe floods or droughts. Under climate change scenarios, the magnitude and frequency of climate extremes is projected to increase meaning that the unprecedented extremes studied here could become commonplace in the future. This suggests that significant investment is needed to develop adaptations that manage the climate-related risks to food systems now and build resilience to the projected impacts of climate change.